On the Trial and Execution of Uguccione della Badia: A Conspiracy in Estense Ferrara? - Tristano, Richard M. (Reti Medievali Rivista, 2022)
In 1460 Uguccione della Badia, long-time secretary and chancellor of Borso d’Este, ruler of Ferrara (1450-1471), was tried and executed for plotting to assassinate his lord. While historians of Ferrara have noted this event, they have not agreed about its significance. Using various texts and contexts, this study compares Uguccione’s plot to other Italian conspiracies, explores the charges against Uguccione, offers explanations for his arrest, and suggests what the matter reveals about the nature of the Estense polity under Borso. Relevant features include the role of bastardy, rebellion, capital punishment, the chancery, foreign policy, and issues of succession particular to the regime. The threats to Estensi rulers were more serious, vigilance more intense, and Borso’s skill in deflecting dangers more accomplished, than previously thought.